The dawn of the Middle Paleolithic in Atapuerca: the lithic assemblage of TD10.1 from Gran Dolina. Issue 145 (August 2020) - de Lombera-Hermida, Arturo; Rodríguez-Álvarez, Xosé Pedro; Mosquera, Marina; Ollé, Andreu; García-Medrano, Paula; Pedergnana, Antonella; Terradillos-Bernal, Marcos; López-Ortega, Esther; Bargalló, Amèlia; Rodríguez-Hidalgo, Antonio; Saladié, Palmira; Bermúdez de Castro, Jose María; et al.
Abstract: The Atapuerca localities present evidence of a long series of hominin occupations from the Early Pleistocene onward and are a key site for understanding the continuity and discontinuity of Western European technological and settlement dynamics. The TD10 unit from Gran Dolina is located in the upper part of the sequence and divided into four lithostratigraphic subunits (TD10.4 to TD10.1, from bottom to top) dated between ca. 450 ka and ca. 250 ka (Marine Isotope Stage 11 to Marine Isotope Stage 8). The technological analysis of the lithic assemblages belonging to the TD10.1 sequence aims to determine the trends among its archeological levels and check its relation to late Middle Pleistocene technological evolution and site functionality. Archeostratigraphic studies have identified several occupation events within its approximately 1.5 m of thickness, whose artifact densities and occupational models differ. However, no remarkable technical differences have been observed among them. Lithic assemblages from those events show more evolved features than other Atapuerca Mode 2 assemblages. These changes are reflected in the selective raw material management strategies; more hierarchized and predetermined reduction methods; and the progressive decrease of large cutting tools in the lithic assemblages with respect to flake tools, the latter defined by a greater typological diversification. These technological changes did not lead to a clear break with respect to previous technological models and were accompanied by other sporadic but significant changes in subsistence and behavioral strategies (bone tools and retouchers; lithic recycling, and so on), which were consolidated during the Middle Paleolithic. Hence, the archeological record from the TD10.1 subunit of Gran Dolina reflects a local stratigraphic transition from Mode 2 to Mode 3 technocomplexes, paralleling that observed in other sites in southwestern Europe.